2001
DOI: 10.1080/02724930020028885
|View full text |Cite
|
Sign up to set email alerts
|

Impact of education and training on neonatal resuscitation practices in 14 teaching hospitals in India

Abstract: The impact of a neonatal resuscitation programme (NRP) on the incidence, management and outcome of birth asphyxia was evaluated in 14 teaching hospitals in India. Two faculty members from each institution attended a neonatal resuscitation certification course and afterwards trained staff in their respective hospitals. Each institution provided 3 months pre-intervention and 12 months post-intervention data. Introduction of the NRP significantly increased awareness and documentation of birth asphyxia, as judged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 4 publications
0
38
0
Order By: Relevance
“…Although NRP training reduces neonatal mortality in controlled, nonrandomized studies in China, India, and Africa [10, 15, 32, 33], the literature surrounding NRP curriculums' impact is not consistent. Our results contribute to that literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although NRP training reduces neonatal mortality in controlled, nonrandomized studies in China, India, and Africa [10, 15, 32, 33], the literature surrounding NRP curriculums' impact is not consistent. Our results contribute to that literature.…”
Section: Discussionmentioning
confidence: 99%
“…Data at the individual patient level could have revealed a statistically significant impact of the LPCH neonatal resuscitation curriculum on neonatal mortality for certain subpopulations of neonates born at St. Gabriel's such as stillbirths. A prospective study, for example, in India found that while neonatal mortality did not decrease following the implementation of neonatal resuscitation programs, asphyxia-related deaths did significantly decline [33]. We were limited in our ability to individually track cases because such data is not collected at St. Gabriel's Hospital; thus, we were unable to compare the two cohorts on variables such as maternal age, prenatal health, and maternal health.…”
Section: Discussionmentioning
confidence: 99%
“…10, 11 However, neonatal resuscitation training has had limited penetration in many LMIC despite findings that when implemented mortality decreases by 20%–50%. 7, 12, 13 …”
mentioning
confidence: 99%
“…About six to 10% of all newly-born infants need some assistance to establish normal breathing at birth. 4–6 Once spontaneous breathing is established, most of these infants survive without requiring further support during the post natal period. 4 …”
mentioning
confidence: 99%